2012
DOI: 10.1080/02640414.2011.627370
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exercise stress impairs volitional but not magnetically evoked electromechanical delay of the knee flexors

Abstract: The effects of serial episodes of fatigue and recovery on volitional and magneticallyevoked neuromuscular performance of the knee flexors were assessed in twenty female soccer players during: (i) an intervention comprising 4x35s maximal static exercise; (ii) a control condition. Volitional peak force (PF V ) was impaired progressively (-16 % vs. baseline: 235.3±54.7 to 198.1±38 However, improved EMD E performance might identify a dormant capability for optimal muscle responses during acute stressful exercise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This study showed that voluntary EMD increased as a result of neuromuscular fatigue for the leg extensors and flexors in both men and women. The increased EMD is similar to the findings of previous studies that also showed fatigue‐inducing increases in EMD for leg extensors, leg flexors, adductor pollicis, plantar flexors, and biceps brachii muscles. Because EMD is a function of both the structural components of the muscle–tendon unit (i.e., SEC, tendon properties) and muscle membrane action potential propagation and EC‐C, the fatigue‐inducing increases in EMD we observed may be a consequence of alterations or impairments in these physiological mechanisms.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This study showed that voluntary EMD increased as a result of neuromuscular fatigue for the leg extensors and flexors in both men and women. The increased EMD is similar to the findings of previous studies that also showed fatigue‐inducing increases in EMD for leg extensors, leg flexors, adductor pollicis, plantar flexors, and biceps brachii muscles. Because EMD is a function of both the structural components of the muscle–tendon unit (i.e., SEC, tendon properties) and muscle membrane action potential propagation and EC‐C, the fatigue‐inducing increases in EMD we observed may be a consequence of alterations or impairments in these physiological mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…The concept of neuromuscular fatigue yielding an increase in voluntary EMD has been acknowledged by Zhou, who observed increased EMD immediately after performing maximum voluntary isometric contractions (MVICs) of the leg extensors. Moreover, previous studies assessing the time course of EMD after a fatiguing task have shown that increased EMD in leg extensors typically returns to baseline within 7–10 min post‐fatigue, while EMD of the leg flexors may remain elevated for up to 8–30 min . Although these findings provide support for potential differences in EMD recovery times between muscles, an increased EMD resulting from fatigue, regardless of the muscles being examined (leg extensors or flexors), may decrease performance and increase the risk of injury .…”
mentioning
confidence: 77%
See 3 more Smart Citations